The geology and geochemistry of the Etendeka Formation quartz latites, Namibia - Milner, Simon Charles; Milner, Simon Charles (Department of Geological Sciences, 2017)
The Etendeka Formation volcanics of north-western Namibia form part of the Karoo Igneous Province of southern Africa and consist of a series of basalts interbedded with quartz latites and minor volumes of latite. This thesis examines various aspects of the geology and geochemistry of the quartz latites, in particular the volcanological and petrogenetic origin of these rocks . This study has involved the geological mapping of ca. 5000 km² of the southern Etendeka region and the documentation of the field and petrographic characteristics of the quartz latites. 183 whole rock quartz latite samples have been analysed for 32 elements by x-ray fluorescence spectrometry and 17 of these samples were selected for detailed mineral analyses by electron microprobe.